Effects of therapist‐worn protective equipment during functional analysis of aggression. Issue 3 (25th March 2018) - Oropeza, Manuella E.; Fritz, Jennifer N.; Nissen, Melissa A.; Terrell, Amy S.; Phillips, Lauren A.
Abstract : The effects of therapist‐worn protective equipment (PE) on functional analysis (FA) outcomes for aggression were evaluated. Independent FAs with and without PE were conducted concurrently. Both FAs showed the same function of aggression for all participants. These results suggest that therapists may wear PE during FAs of aggression to reduce risk without altering the interpretation of the analysis.